Subpixel precision of crack lip movements by Heaviside‐based digital image correlation for a mixed‐mode fracture. (15th April 2020) - Hedan, Stephen; Valle, Valéry; Cosenza, Philippe
Abstract: This study reports on the Heaviside‐based digital image correlation (H‐DIC) procedure and its application in fracture analysis. This improved DIC procedure was proposed to solve the uncertainty problems at the vicinity of the crack and to evaluate the opening and shear movements of crack lips and the orientations of cracks in the subset. Some tests were conducted to demonstrate the performance of the H‐DIC algorithm. An application on argillaceous rock mass exhibiting multiple mixed‐mode fractures is shown to validate the efficiency and robustness of the proposed method. This application consisted in processing images acquired from an experimental investigation performed in a gallery front submitted to climatic seasonal variations. The results illustrated how the H‐DIC procedure enables to localise and to quantify the opening, shearing and orientation of subpixel cracks. A sensibility study performed on the opening and shear components demonstrated that the precision of crack aperture by H‐DIC procedure is close to 0.14 pixel and the spatial resolution is equal to one pixel. Moreover, the crack area was calculated from local apertures on a monitoring duration of 1 year, and a maximum value of 595.8 mm 2 in winter was obtained.